Cultivo Ilegal de la Hoja de Coca y Capacidad de Respuesta del Comando Especial de los Valles de los Rios Apurimac, Ene y Mantaro, Año 2015 - Vargas Sarmiento, Omar Orlando (2018)
The present work, it focuses having in consideration that the current international conjuncture does that the production and the consumption of drugs are topics of great relevancy. The violence in Latin America has increased enormously because of the drugs, process reflected in the level of violence that is suffering Mexico and the countries of Central America. Opposite to this serious problem, which begins with the illegal culture of the leaf of coca, the aim of the present study is to support the management of the Peruvian government in order that by means of the employment of his Armed Forces, particularly the Army and the State police of Peru, develops multiple efforts to strengthen the fight against this illegal culture and for it approach his major effort in the Special Command of the Valleys of the Rivers Apurímac, Ene and Mantaro (CE VRAEM) entrusting him to control the production and to fight for his eradication. The variables of the present study contemplate the illegal culture of the leaf of coca and the capacity of response of the CE VRAEM. The importance of the present investigation is to propose hypothesis of solution across the capacity of response of the CE VRAEM, relating the dimensions of production and eradication of the illegal culture of the leaf of coca, with the dimensions of operations and military actions. The used method has had a quantitative approach, since it was based on a hypothetical deductive and logical scheme, applied and substantive, not experimental investigation, that is to say, has not manipulated any variable. It was an investigation ex-post fact, because it was based on facts and actions that already happened. The technologies selected and applied in this study were: the observation, during situations experienced by the units of analysis, reading and analysis; and the application of a survey (questionnaire). The indicators related to the dimensions production and eradication, show clearly a very narrow relation with other dimensions, operations and military actions